2016
DOI: 10.3109/17453674.2016.1165558
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteria with molecular methods in prosthetic joint infection: sonication fluid better than periprosthetic tissue

Abstract: Background and purposeThe correct diagnosis of prosthetic joint infection (PJI) can be difficult because bacteria form a biofilm on the surface of the implant. The sensitivity of culture from sonication fluid is better than that from periprosthetic tissue, but no comparison studies using molecular methods on a large scale have been performed. We assessed whether periprosthetic tissue or sonication fluid should be used for molecular analysis.Patients and methodsImplant and tissue samples were retrieved from 87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…Sonication of prostheses has proved to be reliable, effective, and reproducible [23,31]. Sonicates of implants have been used in both conventional and molecular microbiological methods, and more frequently than periprosthetic tissues as PCR material for PJI diagnosis, with superior sensitivity [27,32,33]. Our results agree with these studies as the sonicate PCR sensitivity was 64.3% and 71.4% for the conventional and viability PCR respectively compared to 15.4% and 23% for the periprosthetic tissues.…”
Section: Discussionsupporting
confidence: 84%
“…Sonication of prostheses has proved to be reliable, effective, and reproducible [23,31]. Sonicates of implants have been used in both conventional and molecular microbiological methods, and more frequently than periprosthetic tissues as PCR material for PJI diagnosis, with superior sensitivity [27,32,33]. Our results agree with these studies as the sonicate PCR sensitivity was 64.3% and 71.4% for the conventional and viability PCR respectively compared to 15.4% and 23% for the periprosthetic tissues.…”
Section: Discussionsupporting
confidence: 84%
“…A study that compared cultures obtained from sonication fluid and PCR for PJI determined that in patients with prior antibiotic therapy mPCR was positive in 100%, whereas cultures from sonication only in 42% 32 . In further studies could be shown another advantage that PCR of prosthesis sonication samples is more sensitive than tissue culture for the microbiologic diagnosis of PJI and provides same-day diagnosis with definition of microbiology 34 , 35 . In a recent study was stated, that PCR and microarray-based platform provide the attractive possibility of faster bacterial diagnosis than with routine culture, and the molecular methods were most helpful in PJI diagnostics during ongoing antimicrobial treatment 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The great benefit of this PCR technique in diagnosing PJI was documented especially in patients who received antibiotic therapy close to surgery or for a longer period 7 8 . Studies suggest that NAT of sonication fluid may further increase sensitivity and specificity 37 . Unfortunately, this technique is not routinely available in laboratories, due to its time-consuming workflow.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain limitations to the PCR technique in general: NAT detects DNA with no differentiation between viable and non-viable bacteria, making interpretation of the results difficult. Broad-range PCR will only detect ribosomal 16S ribonucleic acid (16S rRNA), not differentiating between pathogens 37 . More specific systems do not routinely detect gene-encoded antibiotic resistance markers.…”
Section: Discussionmentioning
confidence: 99%